Echocardiography predictors of sustained sinus rhythm after cardioversion of supraventricular arrhythmia in patients with septic shock - Balik, M; Waldauf, P; Maly, M; Brozek, T; Rulisek, J; Porizka, M; Sachl, R; Otahal, M; Brestovansky, P; Svobodova, E; Flaksa, M; Stach, Z; et al. (Journal of critical care, 2024)
PURPOSE: The echocardiography parameters may predict the maintenance of sinus rhythm after cardioversion of a supraventricular arrhythmia (SVA). MATERIALS AND METHODS: Patients in septic shock with onset of an SVA, normal to moderately reduced LV systolic function (EF_LV˃̳35%) and on a continuous noradrenaline of <1.0 μg/kg.min were included. Echocardiography was performed at the arrhythmia onset, 1 h and 4 h post cardioversion on an infusion of propafenone or amiodarone. RESULTS: Cardioversion was achieved in 96% of the 209 patients within a median time of 6(1.8-15.6)h, 134(64.1%) patients experienced at least one SVA recurrence after cardioversion. At 4 h the left atrial emptying fraction (LA_EF, cut-off 38.4%, AUC 0.69,p˂0.001), and transmitral A wave velocity-time-integral (Avti, cut-off 6.8 cm, AUC 0.65,p = 0.001) showed as limited predictors of a single arrhythmia recurrence. The LA_EF 44(36,49)%, (p = 0.005) and the Avti 8.65(7.13,9.50)cm, (p < 0.001) were associated with sustained sinus rhythm and decreased proportionally to increasing numbers of arrhythmia recurrences (p < 0.001 and p = 0.007, respectively). The enlarged left atrial end-systolic diameter at the arrhythmia onset (p = 0.04) and elevated systolic pulmonary artery pressure at 4 h (p = 0.007) were weak predictors of multiple(˃3) recurrences. CONCLUSION: The LA_EF and Avti are related to arrhythmia recurrences post-cardioversion suggesting potential guidance to the choice between rhythm and rate control strategies. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT03029169, registered on 24th of January 2017.
Keywords: propafenon; recidiva; Propafenone; Humans; Left atrial emptying fraction; lidé středního věku; elektrická defibrilace; echokardiografie; Amiodarone; Echocardiography; Female; Aged; Trans-mitral a wave; Tachycardia, Supraventricular; senioři; lidé; supraventrikulární tachykardie; septický šok; Electric Countershock; Shock, Septic; Left-atrial end-systolic diameter; ženské pohlaví; Male; Middle Aged; antiarytmika; Anti-Arrhythmia Agents; Recurrence; mužské pohlaví; prospektivní studie; Atrial fibrillation; Left atrial end-systolic volume; amiodaron; A wave velocity-time-integral; Prospective Studies